ASPEK KEMANFAATAN DAN KEPASTIAN HUKUM TERHADAP PUTUSAN MAHKAMAH AGUNG TENTANG BATAS USIA CALON KEPALA DAERAH - Prabowo, Rhesa Yusuf; Wiryadi, Uyan; Bhakti, Teguh Satya (Jurnal Ilmiah Dinamika Hukum, 2025)
Supreme Court Decision Number 23 P/HUM/2024 which annuls PKPU No. 9 of 2020. Supreme Court Decision Number 23 P/HUM/2024 relates to changes in the minimum age requirements for regional head candidates. In the decision, the Supreme Court granted the lawsuit filed by the General Chairperson of the Garuda Party, Ahmad Ridha Sabana, who challenged Article 4 paragraph (1) letter d of PKPU No. 9 of 2020 concerning the Nomination of the Election of Governor, Deputy Governor, Regent, Deputy Regent, Mayor, and Deputy Mayor. The problem is, what are the legal consequences of the Supreme Court Decision Number 23 P/HUM/2024 which annuls PKPU No. 9 of 2020 concerning the fourth amendment to PKPU Number 3 of 2017 concerning the Nomination of the Election of Governor and Deputy Governor, Regent and Deputy Regent, and/or Mayor and Deputy Mayor? How are the Aspects of Benefit and Legal Certainty in the Supreme Court Decision Number 23 P/HUM/2024 regarding the Age Limit for Regional Head Candidates? Normative legal research method. In conclusion, the legal consequences of the Supreme Court Decision Number 23 P/HUM/2024 which revoked PKPU No. 9 of 2020 concerning the Fourth Amendment to PKPU Number 3 of 2017 concerning the Nomination of the Election of Governor and Deputy Governor, Regent and Deputy Regent, and/or Mayor and Deputy Mayor. This decision has various legal implications that not only change the regulatory framework for regional elections, but also raise two (2) problems from the decision, namely: (a) Impact on the hierarchy of laws and regulations; (b) Impact on the nomination process. The Aspects of Benefit and Legal Certainty in the Supreme Court Decision Number 23 P/HUM/2024 regarding the Age Limit for Regional Head Candidates reflect efforts to realize a balance between the aspects of benefit and legal certainty in the general election system in Indonesia. Overall, from the aspect of utility, this decision does not provide a substantive solution to the community's need for clear and inclusive regulations, especially regarding the participation of the younger generation. From the aspect of legal certainty, this decision actually creates a vacuum of norms, opens up opportunities for new disputes, and creates instability in the implementation of regional elections. Thus, although this decision is legally valid, its impact shows weaknesses in creating utility and legal certainty.